Influencing Factors for the Acceptance of 3G Mobile Service in Kathmandu Valley - Taludhar, Anij (Journal of Business and Social Sciences Research, 2018)
The mobile industry in recent years has been growing at a speedy pace where the use of cell phone is no longer limited to conventional usage like the voice communication, but has enriched the customer experiences with mobile internet services and other value added services. Along with the growing mobile industry, technology behind it is also changing accordingly. However, the user acceptance of technology depends on various factors that lead to either user acceptance or rejection. This study thus aims to identify the major determining factors that influence the user to use the 3G mobile internet and examines the interrelation among the determinants along with effect of the demographic variable limited to Kathmandu Valley users. The conceptual framework of this study is based on the extended version of Davis (1989)’s technology acceptance model using variables social influence, price perception, perceived usefulness, perceived ease of use, attitude to use and behavior intention. The primary survey is conducted using a set of questionnaire, which produced 180 valid responses from the mobile users in Kathmandu Valley. The reliability of the data from questionnaire is verified with factor analysis and Cronbach’s alpha. The result shows that social influence has significant influence on perceived ease of use while it has no significant influence on perceived usefulness. Price perception, on the other hand, influences the perceived usefulness. Similarly, perceived usefulness and perceived ease of use influence the attitude of use, which finally influences the behavioral intention. Along with this, social influence is also found to be the extended factors that can influence the attitude of the users, which in turn affects the behavioral intention. Demographic variables, however in this study, have shown no significant influence on the behavioral intentions. On the whole, the usage of 3G mobile internet service is not seen to be satisfying from the study. The major reasons as surveyed from the users themselves for this lower utilization seems to be higher data costs, presence of cheaper alternatives for internet like Wi-Fi internet, quick drainage of battery and slow mobile internet service provided by the mobile service providers. Thus, for mobile service providers, internet service providers are their direct competitors for 3G mobile internet services. This paper enhances understanding of user acceptance of 3G mobile internet services. Journal of Business and Social Sciences Research, Vol. 1, No. 2, pp. 135-152